2007
DOI: 10.1111/j.1540-8159.2007.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Using the Upper Limit of Vulnerability to Assess Defibrillation Efficacy at Implantation of ICDs

Abstract: The upper limit of vulnerability (ULV) is the weakest shock strength at or above which ventricular fibrillation (VF) is not induced when the shock is delivered during the vulnerable period. The ULV, a measurement made in regular rhythm, provides an estimate of the minimum shock strength required for reliable defibrillation that is as accurate or more accurate than the defibrillation threshold (DFT). The ULV hypothesis of defibrillation postulates a mechanistic relationship between the ULV-measured during regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 79 publications
0
59
0
Order By: Relevance
“…Often, VF inductions have been considered necessary in patients with sinus rhythm R-wave amplitudes <5 to 7 mV. 5,6,14 This study found that clinically significant undersensing did not occur in any patient but found sporadic VF undersensing in patients with sinus R-wave amplitudes as large as 13.9 mV and adequate VF sensing in all patients with amplitudes between 3 and 7 mV. A significant number of induced VF episodes (39%) had at least 1 undersensed event, but only half that many (21%) showed at least 2 undersensed events, and the pattern continued for greater numbers of undersensed events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Often, VF inductions have been considered necessary in patients with sinus rhythm R-wave amplitudes <5 to 7 mV. 5,6,14 This study found that clinically significant undersensing did not occur in any patient but found sporadic VF undersensing in patients with sinus R-wave amplitudes as large as 13.9 mV and adequate VF sensing in all patients with amplitudes between 3 and 7 mV. A significant number of induced VF episodes (39%) had at least 1 undersensed event, but only half that many (21%) showed at least 2 undersensed events, and the pattern continued for greater numbers of undersensed events.…”
Section: Discussionmentioning
confidence: 99%
“…In many patients, ICD implant testing can be performed without induction of VF using methods based on the ULV. 5,6,11,14 Clinical assessment of the ULV is performed by delivering shocks coupled to overdrive ventricular pacing trains, usually at 500 ms. The pacing trains are necessary to establish a controlled electrophysiological substrate.…”
Section: Clinical Perspective On P 1080mentioning
confidence: 99%
See 1 more Smart Citation
“…While shock efficacy remains probabilistic, increased confidence in an ICD's ability to successfully terminate spontaneous VAs can be established with defibrillation threshold (DFT) testing. 2 The practice of routine DFT testing at the time of implant has decreased over the years, owing to advancements in ICD technology including improved lead design and higher shock capacity. Several recent randomized trials have shown equivalent clinical outcomes with or without DFT testing at the time of initial transvenous ICD implantation across multiple cardiac substrates.…”
Section: Introductionmentioning
confidence: 99%
“…A close correlation between the ULV and the defibrillation threshold (DFT) has been validated in some studies of humans and other animals, 12-14 and the safety and reliability of ICD implantation and programming of the lower first-shock strength using vulnerability testing without VF induction as a surrogate for DFT assessment has been demonstrated. [15][16][17][18][19][20][21] The present study evaluated the usefulness of vulnerability testing to confirm acceptable DFT at the time of ICD implantation and to predict high DFT (>20 J). Optimal strength and number of shocks at ULV testing to predict high DFT without inducing VF were assessed.…”
mentioning
confidence: 99%